Protein Kinase A Operates a Molecular Switch That Governs Yeast Pseudohyphal Differentiation - Pan, Xuewen (American Society for Microbiology, 2002)
The yeast Saccharomyces cerevisiae undergoes a dimorphic filamentous transition in response to nutrient cues that is affected by both mitogen-activated protein kinase and cyclic AMP-protein kinase A signaling cascades. Here two transcriptional regulators, Flo8 and Sfl1, are shown to be the direct molecular targets of protein kinase A. Flo8 and Sfl1 antagonistically control expression of the cell adhesin Flo11 via a common promoter element. Phosphorylation by the protein kinase A catalytic subunit Tpk2 promotes Flo8 binding and activation of the Flo11 promoter and relieves repression by prohibiting dimerization and DNA binding by Sfl1. Our studies illustrate in molecular detail how protein kinase A combinatorially effects a key developmental switch. Similar mechanisms may operate in pathogenic fungi and more complex multicellular eukaryotic organisms.